Cerebral Embolism due to a Large Papillary Fibroelastoma arising from the Coumadin Ridge. Issue 6 (10th May 2019) - Kamimura, Teppei; Tanaka, Kanta; Yamagami, Hiroshi; Koga, Masatoshi
Abstract: A 70‐year‐old woman developed acute cerebral infarction. Transthoracic echocardiography showed a large mobile mass in the left atrium, suggesting cardiac myxoma as the most likely diagnosis. Surgical exploration revealed a papillary fibroelastoma originating from the coumadin ridge, which is fairly rare but important as a source of cerebral embolization. Abstract : A 70‐year‐old woman developed acute cerebral infarction. Transthoracic echocardiography showed a large mobile mass in the left atrium, suggesting cardiac myxoma as the most likely diagnosis. Surgical exploration revealed a papillary fibroelastoma originating from the coumadin ridge, which is fairly rare but important as a source of cerebral embolization.